Determinants of Behavioral Intention to Use E-Government in Thailand: Mediating Role of Perceived Value of E-Government - Jermsittiparsert, Kittisak; Emiroglu, Talip; Sozudogru, Oytun; Phonwattana, Somsathid; Pungpho, Krissamaporn (Jurnal Politik Indonesia: Indonesian Political Science Review, 2022)
The aim of this study was to know about the impact of social influence (SI), trust worthiness (TW), degree of openness (DO), technological risks (TR) and facilitating conditions (FC) on behavioral intention to use (BIU). This paper also aims to know the mediating role that perceived value of E-governance (PVG). This study was conducted in Thailand. Out of the total 292 respondents of this research, 112 were male and 180 respondents were females, which means that majority of the respondents were females. Out of the total 292 respondents of this research, twenty-three of the respondents had completed their graduation, one hundred and thirty-six respondents had completed their post-graduation, one hundred and twenty-three respondents had completed their masters and ten respondents had other degrees. Out of the total 292 respondents, 230 of the respondents were between the age of 21 to 30 years, 42 were in the age range of 31 to 40 years, 18 were between the age of 41 to 50 years, and lastly 2 were more than 50 years old in age. The research showed that the impact of FC and SI is positive and significant on BIU. Whereas, TR, DO and TW have insignificant impact on BIU. The study also proposed that the mediating role of PVG is significant between FC, TW, TR and BIU is significant. Whereas, the mediating role of PVG between DO, SI and BIU is insignificant.